2021
DOI: 10.1111/jnc.15548
|View full text |Cite
|
Sign up to set email alerts
|

A neurodegeneration gene, WDR45, links impaired ferritinophagy to iron accumulation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 101 publications
2
13
0
Order By: Relevance
“…Patient-derived fibroblasts present lysosomal Fe 2+ accumulation, lysosomal enlargement, and a fragmented mitochondrial network [ 47 ]. WDR45-deficient neuroblastoma cells show impaired ferritinophagy, increased non-Tf bound iron uptake, elevated mitochondrial iron levels, and deficits in mitochondrial respiration [ 48 ]. This phenotype suggests that the inability of cells to obtain the iron stored in ferritin generates a deregulated iron uptake, possibly as a compensatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Patient-derived fibroblasts present lysosomal Fe 2+ accumulation, lysosomal enlargement, and a fragmented mitochondrial network [ 47 ]. WDR45-deficient neuroblastoma cells show impaired ferritinophagy, increased non-Tf bound iron uptake, elevated mitochondrial iron levels, and deficits in mitochondrial respiration [ 48 ]. This phenotype suggests that the inability of cells to obtain the iron stored in ferritin generates a deregulated iron uptake, possibly as a compensatory response.…”
Section: Resultsmentioning
confidence: 99%
“…As a subtype of neurodegeneration with brain iron accumulation (NBIA), iron accumulates in the globus pallidus and substantia nigra [ 3 ]. Several studies have shown that ferritin dysregulation in WDR45 deficient cells consequently disrupts iron homeostasis [ 36 , 43 46 ]. Iron accumulation may lead to ferroptosis, which promotes BPAN; however, treatment with iron chelation drugs has no benefit and can even worsen this process [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of molecular abnormalities led to the hypothesis that mutations in WDR45 may affect ferritinophagy and mitophagy causing deranged Fe recycling with DMT1 upregulation as a proximal cause of Fe accumulation [224]. Impaired ferritinophagy and non-transferrin-bound iron pathway were confirmed to mediate the accumulation of iron in another cellular BPAN model [234] whereby iron was detected mostly in lysosomal vesicles [235]. Yet another study employing the cellular BPAN model found accumulation of TfR in cells overexpressing mutated WDR45 that was associated with increased Fe levels [236].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 96%